Emission characteristics of boron nitride coated carbon nanotubes - Yoo, JB; Han, JH; Choi, SH; Lee, TY; Park, CY; Jeong, TW; Lee, JH; Yu, SG; Park, G; Yi, WK; Kim, HS; Baik, YJ; et al. (ELSEVIER SCIENCE BV, 2002)
Formation and the emission characteristics of boron nitride (BN)-coated carbon nanotubes (CNTs) was investigated. BN films of thickness 3-10 nm were deposited on the vertically aligned CNTs by reactive sputtering. The effect of various pre-treatment of CNTs prior to BN deposition on the emission characteristics was studied. Emission stability of BN-coated CNTs was evaluated in oxygen ambient and compared to that of as-grown CNTs. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: FIELD-EMISSION; DEPOSITION; EMITTERS; BUNDLES